1976
DOI: 10.1111/j.1476-5381.1976.tb07700.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dopamine and Noradrenaline on Isolated Cerebral Arteries of the Dog

Abstract: I Effects of dopamine and noradrenaline were compared in helically-cut strips of canine cerebral arteries.2 Dopamine caused a greater maximal contraction than noradrenaline, although the ED50 for noradrenaline was appreciably less. The contraction induced by these amines was reversed to a relaxation by treatment with phenoxybenzamine. 3 Relaxation induced by dopamine in phenoxybenzamine-treated and prostaglandin-contracted cerebral arteries was not influenced by 1 gM propranolol, while relaxation induced by no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Dopaminergic agonists (such as apomor phine) interact with specific dopaminergic receptors that have been identified on cerebrovascular smooth muscle in vitro and in situ (Toda, 1976;Ed vinsson et ai., 197&l,b), and this direct action upon the cerebral vasculature has been proposed to ac count for the changes in CBF that have been re ported following the administration of dopamine and apomorphine (von Essen, 1974;von Essen and Roos, 1974). However, the administration of dopaminergic agonists (such as amphetamine, apomorphine, and piribedil) results in an increase in cerebral oxygen consumption, and the concomitant increases in CBF that are observed with these agents have been suggested to be a consequence of the increased metabolic demand (McCulloch and Harper, 1977a,b;McCulloch and Edvinsson, 1980).…”
mentioning
confidence: 99%
“…Dopaminergic agonists (such as apomor phine) interact with specific dopaminergic receptors that have been identified on cerebrovascular smooth muscle in vitro and in situ (Toda, 1976;Ed vinsson et ai., 197&l,b), and this direct action upon the cerebral vasculature has been proposed to ac count for the changes in CBF that have been re ported following the administration of dopamine and apomorphine (von Essen, 1974;von Essen and Roos, 1974). However, the administration of dopaminergic agonists (such as amphetamine, apomorphine, and piribedil) results in an increase in cerebral oxygen consumption, and the concomitant increases in CBF that are observed with these agents have been suggested to be a consequence of the increased metabolic demand (McCulloch and Harper, 1977a,b;McCulloch and Edvinsson, 1980).…”
mentioning
confidence: 99%
“…6). (11)(12)(13)(14)(15)(16). Hence, it is not likely that nigral-induced decrease in striatal blood flow in the present experiment is due to a direct effect of dopamine because phentolamine did not affect this decrease.…”
Section: Methodsmentioning
confidence: 63%
“…It is concluded that electrical and chenmical (nicotine-induced) stimulation liberates unknown vasodilator substance(s) possibly from the same site in the arterial wall. Since adenosine 5'-triphosphate (ATP) produces a transient contraction followed by a sustained relaxation (Hayashi, Okunishi, Konishi & Toda, 1979) and the relaxation is suppressed by treatment with aminophylline in cerebral arteries (Toda, 1976b), it seems unlikely that the cerebro-arterial relaxation is mediated by ATP. These results are in agreement with the findings by Lee, Hume, Su & Bevan (1978).…”
Section: Discussionmentioning
confidence: 99%